A Meditator's Diary: A Western Woman's Unique Experiences in Thailand Monasteries - Hamilton-Merritt, Jane (Souvenir Press, 1976)
Keywords: Buddhism; Buddhist meditations; Hamilton-Merritt; Jane; Meditation; dept.his; faculty_collection

A Meditator's Diary: A Western Woman's Unique Experiences in Thailand Temples - Hamilton-Merritt, Jane (Harper & Row, 1976)
Keywords: Buddhism; Hamilton-Merritt; Jane; Meditation; dept.his; faculty_collection

American Pacific Ocean Trade; Its Impact on Foreign Policy and Continental Expansion, 1784-1860 - Caruthers, J. Wade (Exposition Press, 1973)
Keywords: Commerce; History; History; Pacific Area; History; United States; Pacific Area; United States; dept.his; faculty_collection

Walter Reuther, - Tyler, Robert L. (W. B. Eerdmans, 1973)
Keywords: Reuther; Walter; 1907-1970; dept.his; faculty_collection

The History of Kenya Agriculture. - Cone, L. Winston; Lipscomb, J. F. (University Press of Africa, 1972)
Keywords: Agriculture; History; Kenya; dept.his; faculty_collection

The Revenge of Heaven; Journal of a Young Chinese. - Ling, Ken; London, Miriam; Lee, Ta-ling (Putnam, 1972)
Keywords: 1949-; China; Politics and government; dept.his; faculty_collection

American Nativism, 1830-1860 - Leonard, Ira M.; Parmet, Robert D. (Van Nostrand Reinhold, 1971)
Keywords: 1815-1861; Nativism; Immigrants; Politics and government; United States; United States; dept.his; faculty_collection

The Regulators in North Carolina: A Documentary History, 1759-1776. - Powell, William S.; Huhta, James K.; Farnham, Thomas J. (State Dept. of Archives and History, 1971)
Keywords: History; North Carolina; Regulator Insurrection; 1766-1771; Sources; dept.his; faculty_collection

Africana: Holdings of Books and Other African Resource Material in the Hilton C. Buley Library at Southern Connecticut State College - Southern Connecticut State College Library (Hilton C. Buley Library, Southern Connecticut State College, 1971)
Book Title: Africana: holdings of books and other African resource material in the Hilton C. Buley Library at Southern Connecticut State College Edition: Rev. Place: New Haven
Keywords: Africa; Bibliography; Catalogs; Africa; Connecticut; Library resources; New Haven; dept.his; faculty_collection

Gouverneur Morris and the American Revolution, - Mintz, Max M. (University of Oklahoma Press, 1970)
Report for Bachelor of Engineering (Naval Architecture)., ***CD-ROM held at loans desk***
Keywords: 1775-1783; New York (State); 1775-1783; United States; Biography; Legislators; Biography; United States; Foreign relations; History; Morris; Gouverneur; 1752-1816; Statesmen; Politics and government; Revolution; 1775-1783; dept.his; faculty_collection

Lyautey in Morocco: Protectorate Administration, 1912-1925 - Scham, Alan (University of California Press, 1970)
Keywords: Lyautey; Louis Hubert Gonzalve; 1854-1934; Morocco; Politics and government; dept.his; faculty_collection

Weston: The Forging of a Connecticut Town - Farnham, Thomas J. (Published for the Weston Historical Society by Phoenix Pub., 1979)
Keywords: History; Weston (Conn.); dept.his; faculty_collection

Historians and Slavery: A Critical Analysis of Perspectives and Irony in American Slavery, and Other Recent Works. - Wright, W. D. (1978)
Keywords: Genovese; Eugene D.; 1930-2012; Engerman; Stanley L; Perspectives and irony in American slavery; Slavery; Historiography; United States; dept.his; faculty_collection

Urban legacy: the story of America's cities - Klebanow, Diana (New American Library, 1977)
Keywords: Cities and towns; History; United States; dept.his; faculty_collection

Socio/Psycholinguistics of the cultural revolution: an empirical study - London, Ivan D.; Lee, Ta-Ling (Psychological Reports, 1977)
2 citations (Crossref) [2023-10-31] Citation Key Alias: pop00127 tex.type: [object Object]
Keywords: dept.his

Review of Desperate Diplomacy: William H. Seward's Foreign Policy, 1861 - Farnham, Thomas J. (The Journal of Southern History, 1977)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1977DR88500029 tex.unique-id: [object Object]
Keywords: dept.his

War and Government in Habsburg Spain, 1560-1620 - Thompson,iaa - Stewart, P (American Historical Review, 1977)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1977DY89600114
Keywords: dept.his

Book Review: E. J. Murphy, History of African Civilization. New York, Crowell, 1972, pp. 430, xxlv, maps, plates, $ 14.35 - Cone, L. Winston (Journal of Asian and African Studies, 1975)
"E. J. Murphy, History of African Civilization. New York, Crowell, 1972, pp. 430, xxlv, maps, plates, $ 14.35" published on 01 Jan 1975 by Brill.
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1975BS51300013, lens.org/075-687-014-811-491, pop00255 tex.type: [object Object] tex.unique-id: [object Object]
Keywords: book.review; dept.his

Works of Williams,r,sir - Evans,jx - Stewart, P (American Historical Review, 1973)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1973P376900037
Keywords: dept.his

Review of The Birth of Modern America, 1820-1850 - Farnham, Thomas J. (The Journal of Southern History, 1972)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1972L542200027 tex.unique-id: [object Object]
Keywords: dept.his

Devaldes,j and Origins of Spanish and Italian Reformation - Spanish - Nieto,jc - Stewart, P (American Historical Review, 1971)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1971K587500077
Keywords: dept.his

An eighteenth-century case of plagiarism: william smith's A new voyage to guinea - Feinberg, Harvey M. (History in Africa, 1979)
1 citations (Crossref) [2023-10-31] Citation Key Alias: pop00173 tex.type: [object Object]
Keywords: dept.his

Nietzsche and eschatology - Ausmus, Harry J. (The Journal of Religion, 1978)
1 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1978GA15000001 tex.unique-id: [object Object]
Keywords: dept.his

Book Review: Visions of Utopia: Nashoba, Rugby, Ruskin, and the “New Communities” in Tennessee's Past. By John Egerton. (Knoxville: University of Tennessee Press, Tennessee Historical Commission, 1977. 95 pp. Maps, illustrations, more resources, and index. Paper, $3.50.) - Caruthers, J. Wade (Journal of American History, 1978)
J. Wade Caruthers; Visions of Utopia: Nashoba, Rugby, Ruskin, and the “New Communities” in Tennessee's Past. By John Egerton. (Knoxville: University of Tenness
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1978FQ74200055 tex.unique-id: [object Object]
Keywords: book.review; dept.his

Review of The Encyclopaedia Africana Dictionary of African Biography, Volume I: Ethiopia-Ghana - Feinberg, Harvey M. (The International Journal of African Historical Studies, 1978)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1978FX50100026 tex.unique-id: [object Object]
Keywords: dept.his

Plant Liberation - Struggle Against Fauna Chauvinism - Tyler, RL (Humanist, 1978)
tex.unique-id: ISI:A1978EH64300010
Keywords: dept.his; ⛔ No DOI found

Review of Trade and Economic Change on the Gold Coast, 1807-1874 - Feinberg, H.M. (The International Journal of African Historical Studies, 1977)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1977EA17900031 tex.unique-id: [object Object]
Keywords: dept.his

Schopenhauer's view of history: A note - Ausmus, Harry J. (History and Theory, 1976)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1976BQ84700003 tex.unique-id: [object Object]
Keywords: dept.his

There Was an Elmina Note, But.... - Feinberg, H.M. (The International Journal of African Historical Studies, 1976)
2 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1976DG10400005 tex.unique-id: [object Object]
Keywords: dept.his

Confessions of a Closet Househusband - Tyler, RL (Humanist, 1976)
tex.unique-id: ISI:A1976CL09000010
Keywords: dept.his; ⛔ No DOI found

Review of Akwapim Handbook - Feinberg, H. M. (The International Journal of African Historical Studies, 1975)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1975BF75200071 tex.unique-id: [object Object]
Keywords: dept.his

Boredom and Treadmill of Doing - Tyler, RL (Humanist, 1975)
tex.unique-id: ISI:A1975AW55800006
Keywords: dept.his; ⛔ No DOI found

New data on European mortality in West Africa: the Dutch on the Gold Coast, 1719-1760. - Feinberg, Harvey M (The Journal of African History, 1974)
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/047-758-033-564-756 tex.type: [object Object]
Keywords: dept.his

Review of Colonial Governors from the Fifteenth Century to the Present. A Comprehensive List - Feinberg, H. M. (The International Journal of African Historical Studies, 1973)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1973Q366200015 tex.unique-id: [object Object]
Keywords: dept.his

Consciousness Iv - or Let Us Not Envy Young - Tyler, RL (Humanist, 1972)
tex.unique-id: ISI:A1972Z026200008
Keywords: dept.his; ⛔ No DOI found

Old Siwash Is Not Our Beacon - Tyler, RL (Journal of General Education, 1972)
tex.unique-id: ISI:A1972L436800003
Keywords: dept.his; ⛔ No DOI found

Book Review: Mill town: A social history of everett, washington, from its earliest beginnings on the shores of puget sound to the tragic and infamous event known as the everett massacre. by norman h. clark. (seattle: university of washington press, 1970. x + 267 pp. illustrations, notes, and index. 7.95.) - Tyler, Robert (The Journal of American History, 1972)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/080-427-398-728-100 tex.type: [object Object]
Keywords: book.review; dept.his

Review of Benin and the Europeans 1485-1897 - Feinberg, H. M. (African Historical Studies, 1971)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1971Y060400021 tex.unique-id: [object Object]
Keywords: dept.his

Review of Trade and Politics on the Gold Coast: 1600-1720. A Study of the African Reaction to European Trade - Feinberg, H. M. (African Historical Studies, 1971)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1971Y060500019 tex.unique-id: [object Object]
Keywords: dept.his

Pornos and Prudes Unite - Tyler, RL (Humanist, 1971)
tex.unique-id: ISI:A1971Y044900011
Keywords: dept.his; ⛔ No DOI found

An Incident in Elmina-Dutch Relations, The Gold Coast (Ghana), 1739-1740 - Feinberg, H. M. (African Historical Studies, 1970)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1970Y060200006 tex.unique-id: [object Object]
Keywords: dept.his

Review of West African Trade and Coast Society: A Family Study - Feinberg, H. M. (African Historical Studies, 1970)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1970Y060200027 tex.unique-id: [object Object]
Keywords: dept.his

2-Marriage Revolving-Mate Generation-Bridging Plan to Save Marriage - Tyler, RL (Humanist, 1970)
tex.unique-id: ISI:A1970Y053400012
Keywords: dept.his; ⛔ No DOI found